Diseño de una campaña para una sexualidad responsable en adolescentes de 12- 15 años, para su validación en un colegio de la ciudad de Quito. - Flores López, Ximena Elizabeth (2013)
The problem of teenage pregnancy is one of the major problems both socially and health in Ecuador, especially in adolescents with low levels of education, low income and living in rural or remote areas. A problem that despite the efforts of various agencies both global and local face it, better results have failed to reduce the high rate of teenage pregnancy as a goal to eradicate achieve long-term proposal. So, to ascertain how to develop this reality of teenage pregnancies in the local environment, this project focuses on Marcelino Champagnat College, located south of the city of Quito.